Cubes of finite vertices fuzzy topographic topological mapping and k-Fibonacci sequence - Azrul Azim Mohd Yunus; Ahmad T. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by WOS/SCOPUS